Fire star - D'Lacey, Chris (New York : Orchard Books, 2008)
David Rain is faced with the most perilous task yet when Gwilanna returns, this time determined to resurrect the dragon Gawain on the ice cap of the Tooth of Ragnar, unless David and her friends can stop her.
Sequel to: Icefire.
Sequel: The Fire Eternal.
G6
Keywords: Paranormal fiction; Bears -- Juvenile fiction; Dragons -- Juvenile fiction; Authorship -- Juvenile fiction; Boardinghouses -- Juvenile fiction; Arctic Regions -- Juvenile fiction